Chemical constituents from Carica papaya Linn. leaves as potential cytotoxic, EGFRwt and aromatase (CYP19A) inhibitors; a study supported by molecular docking. Issue 15 (23rd March 2022) - Hamed, Ashraf N. E.; Abouelela, Mohamed E.; El Zowalaty, Ahmed E.; Badr, Mohamed M.; Abdelkader, Mohamed S. A.
Abstract : The phytochemical investigation of the hydromethanolic extract of Carica papaya Linn. leaves (Caricaceae) resulted in the isolation and characterization of ten compounds. Abstract : The phytochemical investigation of the hydromethanolic extract of Carica papaya Linn. leaves (Caricaceae) resulted in the isolation and characterization of ten compounds, namely; carpaine (1 ), methyl gallate (2 ), loliolide (3 ), rutin (4 ), clitorin (5 ), kaempferol-3- O -neohesperidoside (6 ), isoquercetin (7 ), nicotiflorin (8 ) and isorhamnetin-3- O -β-d -glucopyranoside (9 ). The compounds 2, 3, 5–7 and 9 were isolated for the first time from the genus Carica . An in vitro breast cancer cytotoxicity study was evaluated with an MCF-7 cell line using the MTT assay. Methyl gallate and clitorin demonstrated the most potent cytotoxic activities with an IC50 of 1.11 ± 0.06 and 2.47 ± 0.14 μM, respectively. Moreover, methyl gallate and nicotiflorin exhibited potential EGFR wt kinase inhibition activities with an IC50 of 37.3 ± 1.9 and 41.08 ± 2.1 nM, respectively, compared with the positive control erlotinib (IC50 = 35.94 ± 1.8 nM). On the other hand, clitorin and nicotiflorin displayed the strongest aromatase kinase inhibition activities with an IC50 of 77.41 ± 4.53 and 92.84 ± 5.44 nM, respectively. Clitorin was comparable to the efficacy of the standard drug letrozole (IC50 = 77.72 ± 4.55). Additionally, molecular docking simulations of the isolated compounds to EGFR and human placental aromatase cytochrome P450 (CYP19A1) were evaluated. Methyl gallate linked with the EGFR receptor through hydrogen bonding with a pose score of −4.5287 kcal mol −1 and RMSD value of 1.69 Å. Clitorin showed the strongest interaction with aromatase (CYP19A1) for the breast cancer receptor with a posing score of −14.2074 and RMSD value of 1.56 Å. Compounds (1–3 ) possessed a good bioavailability score with a 0.55 value.